2021
DOI: 10.1002/anie.202113077
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Selectivity and Stability of Finned Ferrierite Catalysts in Butene Isomerization

Abstract: Designing zeolite catalysts with improved mass transport properties is crucial for restrictive networks of either one-or two-dimensional pore topologies. Here, we demonstrate the synthesis of finned ferrierite (FER), a commercial zeolite with two-dimensional pores, where protrusions on crystal surfaces behave as pseudo nanoparticles. Catalytic tests of 1-butene isomerization reveal a 3-fold enhancement of catalyst lifetime and an increase of 12 % selectivity to isobutene for finned samples compared to correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Three basic mechanisms of layered zeolite synthesis are well established and commonly used to prepare both aluminosilicate and other metal-substituted zeolites, 22,26,33,65 namely (i) bottom-up crystallization of specific zeolites through layered precursors, (e.g., MWW, FER, and CDO, among others); (ii) surfactant-restricted crystal growth, whereby an appropriate surfactant template blocks crystal growth in one of the crystallographic directions (e.g., MFI); 23 and (iii) top-down transformation of zeolites with structural weaknesses (germanium-rich double-4-ring units) in such positions that their removal transforms an originally 3D zeolite structure into a layered material (e.g., UTL, IWR, and IWW, among others). 24 Except for products from surfactant-restricted crystal growth (ii), zeolite layers can be (re)connected into fully connected 3D zeolite structures.…”
Section: The Diffusion Issue: Varying Catalyst Morphology and Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…Three basic mechanisms of layered zeolite synthesis are well established and commonly used to prepare both aluminosilicate and other metal-substituted zeolites, 22,26,33,65 namely (i) bottom-up crystallization of specific zeolites through layered precursors, (e.g., MWW, FER, and CDO, among others); (ii) surfactant-restricted crystal growth, whereby an appropriate surfactant template blocks crystal growth in one of the crystallographic directions (e.g., MFI); 23 and (iii) top-down transformation of zeolites with structural weaknesses (germanium-rich double-4-ring units) in such positions that their removal transforms an originally 3D zeolite structure into a layered material (e.g., UTL, IWR, and IWW, among others). 24 Except for products from surfactant-restricted crystal growth (ii), zeolite layers can be (re)connected into fully connected 3D zeolite structures.…”
Section: The Diffusion Issue: Varying Catalyst Morphology and Porositymentioning
confidence: 99%
“…These compounds control the formation of mesopores . Demetalation, usually dealumination or desilication, can lead to hierarchical zeolites through an appropriate treatment in acidic or basic solutions, respectively. Experiments recently performed by Rimer and colleagues showed that fins in ferrierite structures increase the transport rates of reactants and products in butane skeletal isomerization.…”
Section: Catalyst Classificationmentioning
confidence: 99%
“…Furthermore, the hierarchical-like structure with stacking along the b -axis has been depicted, as shown in Figure b–d; this structural arrangement facilitates a reduction in diffusion limitations and allows a certain degree of PDH performance optimization. To better illustrate this point, a probe molecule 2,3-dimethylpyridine (DMPyr) containing two methyl groups showed slow diffusion in the MFI 10-MR channel, allowing time-resolved comparisons of the titration of acid sites within the bulk and hierarchical-like phase catalysts (Pt/Fe-1 vs Pt/Fe-3) . Additionally, peaks at around 1635 cm –1 were observed for both Pt/Fe-1 and Pt/Fe-3 during titration attributed to the Lewis acid site, with higher L acid amounts obtained in the first 10 min because of the larger surface area of Pt/Fe-1 (Figure S15).…”
Section: Resultsmentioning
confidence: 99%
“…To better illustrate this point, a probe molecule 2,3-dimethylpyridine (DMPyr) containing two methyl groups showed slow diffusion in the MFI 10-MR channel, allowing time-resolved comparisons of the titration of acid sites within the bulk and hierarchical-like phase catalysts (Pt/Fe-1 vs Pt/Fe-3). 18 Additionally, peaks at around 1635 cm −1 were observed for both Pt/Fe-1 and Pt/Fe-3 during titration attributed to the Lewis acid site, with higher L acid amounts obtained in the first 10 min because of the larger surface area of Pt/Fe-1 (Figure S15). Moreover, a pronounced increase in the L acid amount with Pt/Fe-3 was noticed as time progressed, suggesting better diffusion properties of the 2e−i.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Corma et al found that the modified molecular sieve of Al-rich ZSM-5 can significantly improve the selectivity of methanol conversion to propylene by adjusting the location and distribution of Al species within the pore channel . From the perspective of the pore structure and morphological regulation, a series of newly developed zeolites, such as the platelike ZSM-5 with a shorter b axis designed by Li et al or spontaneous pillaring zeolite and finned zeolite synthesized by Rimer et al, have shown better active site accessibilities and diffusion properties, which could have great potential to enhance the catalytic activity of polyolefin cracking. On the other hand, designing a hierarchical zeolite catalyst is a good strategy. The ratio or the connectivity between micropores and mesopores may profoundly affect the selectivity and stability.…”
Section: Discussionmentioning
confidence: 99%